A Case of Eosinophilic Granulomatosis with Polyangiitis Complicated with A IgG4 Related Disease Like Symptoms - Suguru Sato; Julia Morimoto; Yasuharu Oguchi; Takashi Umeda; Takaya Kawamata; Mami Rikimaru; Tatsuhiko Koizumi; Ryuichi Togawa; Yasuhito Suzuki; Yuki Sato; Manabu Uematsu; Hiroyuki Minemura; et al. (Case Reports in Immunology)
We report a case of eosinophilic granulomatosis with polyangiitis (EGPA) complicated with a IgG4 related disease like symptoms presenting as eyelid swellings. In the present case, the serum level of IgG4 and the ratio of IgG4 to IgG were generally increased by the disease course of EGPA. Considering the course of clinical symptoms, there is a possibility that orbital manifestations were one of the clinical features during the disease course of EGPA while the histological features of right eyelid tissue and other ocular manifestations were consistent with the diagnosis of IgG4 related disease.